3 Post-Coronavirus Opportunities for Students. (12th August 2020) - Whitby, Blay
Abstract: A global pandemic is a traumatic place to be. Among many other things, the fact that the university is physically closed may promote worries about the progress of your degree, writes Blay Whitby MBCS, Lecturer in Cognitive Science for the University of Sussex.